Mutation and phenotypic spectrum in patients with cardio-facio-cutaneous and Costello syndrome - Schulz, A. L; Albrecht, B; Arici, C; van der Burgt, I; Buske, A; Gillessen-Kaesbach, G; Heller, R; Horn, D; Hubner, C. A; Korenke, G. C; Konig, R; Kress, W; et al. (Clinical genetics, 2008)
Cardio-facio-cutaneous (CFC) and Costello syndrome (CS) are congenital disorders with a significant clinical overlap. The recent discovery of heterozygous mutations in genes encoding components of the RAS-RAF-MAPK pathway in both CFC and CS suggested a similar underlying pathogenesis of these two disorders. While CFC is heterogeneous with mutations in BRAF, MAP2K1, MAP2K2 and KRAS, HRAS alterations are almost exclusively associated with CS. We carried out a comprehensive mutation analysis in 51 CFC-affected patients and 31 individuals with CS. Twelve different BRAF alterations were found in twenty-four patients with CFC (47.0%), two MAP2K1 mutations in five (9.8%) and two MAP2K2 sequence variations in three CFC-affected individuals (5.9%), whereas three patients had a KRAS alteration (5.9%). We identified four different missense mutations of HRAS in twenty-eight cases with CS (90.3%), while KRAS mutations were detected in two infants with a phenotype meeting criteria for CS (6.5%). In 14 informative families, we traced the parental origin of HRAS alterations and demonstrated inheritance of the mutated allele exclusively from the father, further confirming a paternal bias in the parental origin of HRAS mutations in CS. Careful clinical evaluation of patients with BRAF and MAP2K1/2 alterations revealed the presence of slight phenotypic differences regarding craniofacial features in MAP2K1- and MAP2K2-mutation positive individuals, suggesting possible genotype-phenotype correlations.
Keywords: mutace; dospělí; Phenotype; ras Proteins; dítě; protoonkogenní proteiny B-raf; Heart Defects, Congenital; Facies; Adult; ras proteiny; mutační analýza DNA; MAP kinasa-kinasa 1; lidé; MAP Kinase Kinase 1; mnohočetné abnormality; DNA Mutational Analysis; Mutation; MAP kinasa-kinasa 2; protoonkogenní proteiny; Intellectual Disability; Proto-Oncogene Proteins B-raf; Developmental Disabilities; Skin Abnormalities; kožní abnormality; vývojové poruchy u dětí; Proto-Oncogene Proteins; Abnormalities, Multiple; Syndrome; Child; vrozené srdeční vady; fenotyp; MAP Kinase Kinase 2; mentální retardace; faciální stigmatizace; syndrom; Humans